The aspects of reproduction of Clathrus archeri (Berk.) Dring by re-situ method in the National Nature Park Hutsulshchyna - Tsvyd, Nadiia; Pasaylyuk, Mariia; Petrichuk, Yurii; Sukhomlyn, Maryna (Leśne Prace Badawcze, 2018)
The biodiversity preservation is one of the main missions on present days. Two main trends of biodiversity conservation in-situ and ex-situ are known today. However, use of both these methods is not enough for the protection of rare species of macromycetes. Therefore, we need a new method for protecting the rare species of fungi, which support their vital process in not only the laboratory but also reproducing it in nature.In this article, we propose the use of a new method of preserving the rare species of fungi in nature. The re-situ is a method that provides introducing and support of vital functions of mushroom in nature with the forming of their basidioma.For our research, we used Clathrus archeri (Berk.) Dring, which is included in the Red Data Book of Ukraine.It was found that the substrate on which the mycelium was grown and subsequently used for natural conditions had a significant influence on the success of ‘reinoculation’ of C. archeri. Among all the investigated substrates, only one (beech shavings) proved to be suitable for growing of sowing mycelium of C. archeri. The research showed that the reproduction of C. archeri in nature should be held on non-forest experimental sites, mainly on meadows during the spring months.